Measurement of the Λ b 0 lifetime in the decay Λ b 0 → J/ψΛ 0 with the D0 detector - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Society (APS), 2005)
We present measurements of the Λ b 0 lifetime in the exclusive decay channel Λ b 0 → J/ψΛ 0with J/ψ → μ +μ - and Λ 0 → pπ -, the B 0 lifetime in the decay B 0 → J/ψ/K s 0 with J/ ψ → μ + μ - and K s 0 → π + π -, and the ratio of these lifetimes. The analysis is based on approximately 250 pb -1 of data recorded with the D0 detector in pp̄ collisions at √s = 1.96 TeV. The Λ b 0 lifetime is determined to be τ(Λ b 0) = 1.22 -0.18 +0.22(stat) ± 0.04(syst) ps, the B 0 lifetime τ(B 0) = 1.40 -0.10 0.11(stat) ± 0.03(syst) ps, and the ratio τ(Λ b 0)/ τ(B 0) = 0.87- 0.14 0.17(stat) ± 0.03(syst). In contrast with previous measurements using semileptonic decays, this is the first determination of the Λ b 0 lifetime based on a fully reconstructed decay channel. © 2005 The American Physical Society.